An examination of the relation between the level of loneliness and internet addiction with regard to the purpose of social network use in university students - Bardak, Furkan; Yalçınkaya Alkar, Özden (Journal of Dependence, 2016)
This study aims to examine the relationships between the level of loneliness, and internet addiction, according to social networks use and how these variables differed by gender. The sample of the study was 348 university students (144 males, 204 females) composed of different universities in Ankara. Demographic information form, Internet Addiction Scale, the Scale of Aims of Use of Social Network Sites, UCLA Loneliness Scale were used to collect data for the study. The data were analyzed by using SPSS-20 program with use of T tests, regression analysis and descriptive statistics. The results of the study showed that there are relationships between the different purposes of social networks use (social interaction and communication, knowing and being known, and educational) and internet addiction. Additionally, there were relationship between knowing and being known and educational purposes of social network use and level of loneliness. In terms of gender, level of loneliness and internet addiction was higher in males than females. While men use social network for the purpose of knowing and being known more than women, women use social networks for educational purposes more compared to men.
Keywords: Internet addiction; social networks use; loneliness